The long non-coding RNA ANRASSF1 in the regulation of alternative protein-coding transcripts RASSF1A and RASSF1C in human breast cancer cells: implications to epigenetic therapy - Calanca, Naiade [UNESP] (2019)
Alternative protein-coding transcripts of the RASSF1 gene have been associated with dual functions in human cancer: while RASSF1C isoform has oncogenic properties, RASSF1A is a tumour suppressor frequently silenced by hypermethylation. Recently, the antisense long non-coding RNA RASSF1 (ANRASSF1) was implicated in a locus-specific mechanism for the RASSF1A epigenetic repression mediated by PRC2 (Polycomb Repressive Complex 2). Here, we evaluated the methylation patterns of the promoter regions of RASSF1A and RASSF1C and the expression levels of these RASSF1 transcripts in breast cancer and breast cancer cell lines. As expected, RASSF1C remained unmethylated and RASSF1A was hypermethylated at high frequencies in 75 primary breast cancers, and also in a panel of three mammary epithelial cells (MEC) and 10 breast cancer cell lines (BCC). Although RASSF1C was expressed in all cell lines, only two of them expressed the transcript RASSF1A. ANRASSF1 expression levels were increased in six BCCs. In vitro induced demethylation with 5-Aza-2ʹ-deoxicytydine (5-Aza-dC) resulted in up-regulation of RASSF1A and an inverse correlation with ANRASSF1 relative abundance in BCCs. However, increased levels of both transcripts were observed in two MECs (184A1 and MCF10A) after treatment with 5-Aza-dC. Overall, these findings indicate that ANRASSF1 is differentially expressed in MECs and BCCs. The lncRNA ANRASSF1 provides new perspectives as a therapeutic target for locus-specific regulation of RASSF1A.